Volumetric and viscometric study with FT-IR analysis of binary systems with diethyl succinate and alcohols. (October 2016) - Majstorović, Divna M.; Živković, Emila M.; Mitrović, Aleksandra D.; Munćan, Jelena S.; Kijevčanin, Mirjana Lj.
Highlights: Densities of three binary mixtures with diethyl succinate and alcohols are measured. Viscosities of three binary mixtures with diethyl succinate and alcohols are given. Excess and deviation functions have been calculated. Fourier transform infrared (FT-IR) spectroscopy analysis has been conducted. Molecular interactions present in the mixture have been analyzed. Abstract: Density, viscosity and refractive index of binary mixtures consisting of diethyl succinate + 1-propanol, or +1-butanol, or +1-hexanol have been measured at atmospheric pressure and over the temperature range from 288.15 K to 323.15 K. Excess and deviation functions have been calculated from these data and fitted to the Redlich-Kister equation. The values of excess molar volume and deviation functions, with Fourier transform infrared (FT-IR) spectroscopy, were further used in the analysis of molecular interactions present in the mixture as well as the temperature influence on them.